Hanford radiation study III: a cohort study of the cancer risks from radiation to workers at Hanford (1944-77 deaths) by the method of regression models in life-tables. - Kneale, G W (1981)
This paper reports on results from the study initiated by Mancuso into the health risks from low-level radiation in workers engaged in plutonium manufacture at Hanford Works, Washington State, USA, and attempts to answer criticisms of previous reports by an in-depth study. Previous reports have aroused much controversy because the reported risk per unit radiation dose for cancers of radiosensitive tissues was much greater than the risk generally accepted on the basis of other studies and widely used in setting safety levels for exposure to low-level radiation. The method of regression models in life-tables isolates the effect of radiation after statistically controlling for a wide range of possible interfering factors. Like the risk of lung cancer for uranium miners the dose-response relation showed a significant downward curve at about 10 rem. There may, therefore, be better agreement with other studies, conduct at higher doses, than is widely assumed. The findings on cancer latency (of about 25 years) and the effect of exposure age (increasing age increases the risk) are in general agreement with other studies. An unexplained finding is a significantly higher dose for all workers who developed cancers in tissues that are supposed to have low sensitivity to cancer induction by radiation.